Sustaining an interprofessional culture of research and evaluation within a community parenting and early childhood organisation - Bennett, Elaine; Simpson, Wendy; Cooke, Dawson; Banham, Vicki; Strange, Cecily; Munns, Ailsa (2021)
Ngala is an evidence-informed community-based parenting and early childhood organisation in Western Australia. During 2007, a strategic decision was made to forge formal links with universities where researchers could actively participate in the establishment of a research agenda that supported identified priority areas for Ngala. This decision provided strategies for embracing the challenges of evidence-informed practice (EIP) for the organisation alongside competing financial demands which, for many not-for-profit organisations, is an ongoing dilemma. This paper will discuss the identified trends, changes and examples which informed the foundational components to sustain a research and evaluation culture within an evidence informed community service organisation (CSO). A case study design was used to describe activity and experiences over a decade. Participants included academics from a range of disciplines, and Ngala managers and practitioners. Multiple data sources were analysed – current literature, an audit of organisational documents, and a leadership survey to establish key components necessary to sustain a research culture. Challenges are described as well as examples of success that enabled growth and change. The sustainability of a culture results in the strength of an organisation to continue building on successes of the past and to focus on the long term. In today’s environment of funders requiring organisations to demonstrate the difference they are making for families with children, it is even more crucial for services to build in resources for research and evaluation, despite growing costs. Senior level leadership and commitment enhances the drive for EIP which takes a whole of organisation approach for sustainability.